2011
DOI: 10.1021/ml100253p
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 4′′-Ether Linked Azithromycin-Quinolone Hybrid Series: Influence of the Central Linker on the Antibacterial Activity

Abstract: A series of novel C-4′′-substituted azithromycins was synthesized and evaluated for in vitro antibacterial activity against a panel of representative erythromycin-susceptible and macrolide-lincosamide-streptogramin (MLS) resistant pathogens. In summary, azithromycin and quinolone substructures merged in a mutually SAR-compatible design gave rise to a new class of antimicrobials with an improved spectrum and potency over azithromycin. Prototypical analogues 7f and 8f display an improved potency versus azithromy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Antibacterial activities of the hybrids were tested on S. aureus , Streptococcus pneumoniae , and S. pyogenes. Most of the conjugates were poorly active; however, compound 56c exhibited the highest antibacterial activity against tested strains [ 138 ].
…”
Section: Hybrid Drugsmentioning
confidence: 99%
“…Antibacterial activities of the hybrids were tested on S. aureus , Streptococcus pneumoniae , and S. pyogenes. Most of the conjugates were poorly active; however, compound 56c exhibited the highest antibacterial activity against tested strains [ 138 ].
…”
Section: Hybrid Drugsmentioning
confidence: 99%
“…Several macrolide‐quinolone hybrids tethered with ester‐amino , ester‐alkynyl , ether‐amino , ester‐alkyl , and ether‐alkyl through C‐6 position of quinolone motif were assessed for their antibacterial potency against both Gram‐positive and Gram‐negative bacteria. The SAR indicated that the antibacterial activity against Gram‐positive pathogens was more potent than against Gram‐negative pathogens generally; the linkers between macrolide moiety and quinolone motif played an important role for the antibacterial activity, especially against Gram‐positive organisms; in general, alkyl‐tethered quinolone hybrids were more active than other linkers against Gram‐negative bacteria as evidenced by ester‐alkyl linked 12 and ether‐alkyl linked 13 .…”
Section: Structure–activity Relationshipmentioning
confidence: 99%
“…s dva dušika u veznom lancu, 19 dok su se kasnije pokazali bolji s jednim ili više kisika. 20,21,22,23 S kolegama iz Verone smo objavili još neke zaostale rezultate.…”
Section: Razdoblje 1996 -2003 Godine Prijelaz Na Bazična Istraživanunclassified